BnaC7.ROT3, the causal gene of cqSL-C7, mediates silique length by affecting cell elongation in Brassica napus. (6th September 2021) - Zhou, Xianming; Zhang, Haiyan; Wang, Pengfei; Liu, Ying; Zhang, Xiaohui; Song, Yixian; Wang, Zhaoyang; Ali, Ahmad; Wan, Lili; Yang, Guangsheng; Hong, Dengfeng
Abstract : A single-nucleotide deletion in BnaC7.ROT3 confers a novel quantitative variation of silique length in Brassica napus . Abstract: Siliques are a major carbohydrate source of energy for later seed development in rapeseed ( Brassica napus ). Thus, silique length has received great attention from breeders. We previously detected a novel quantitative trait locus cqSL-C7 that controls silique length in B. napus . Here, we further validated the cqSL-C7 locus and isolated its causal gene ( BnaC7.ROT3 ) by map-based cloning. In 'Zhongshuang11' (parent line with long siliques), BnaC7.ROT3 encodes the potential cytochrome P450 monooxygenase CYP90C1, whereas in 'G120' (parent line with short siliques), a single nucleotide deletion in the fifth exon of BnaC7.ROT3 results in a loss-of-function truncated protein. Sub-cellular localization and expression pattern analysis revealed that BnaC7.ROT3 is a membrane-localized protein mainly expressed in leaves, flowers and siliques. Cytological observations showed that the cells in silique walls of BnaC7.ROT3 -transformed positive plants were longer than those of transgene-negative plants in the background of 'G120', suggesting that BnaC7.ROT3 affects cell elongation. Haplotype analysis demonstrated that most alleles of BnaC7.ROT3 are favorable in B. napus germplasms, and its homologs may also be involved in silique length regulation. Our findings provide novel insights into the regulatory mechanisms of natural silique length variations and valuable genetic resources for the improvement of silique length in rapeseed.